Biggs on finance, economics, and the stock market : Barton's market chronicles from the Morgan Stanley years - Biggs, Barton, 1932-2012 (Wiley, 2014)
Released to the public for the first time, writings by the incomparable Barton Biggs Long considered one of the best brains on Wall Street, Barton Biggs acquired the stature of a legend within his lifetime. Among his many coups, he accurately called the rise and fall of the dot-com market, and was an energetic promoter of emerging markets, including China, well before American businesses began flocking there-and he made vast fortunes for his clients, in the process. But, as this fascinating book confirms, it wasn't Biggs's genius as a market analyst and hedge fund manager alone that.